Arabidopsis thaliana root cell wall proteomics: Increasing the proteome coverage using a combinatorial peptide ligand library and description of unexpected Hyp in peroxidase amino acid sequences. Issue 3 (February 2016) - Nguyen‐Kim, Huan; San Clemente, Hélène; Balliau, Thierry; Zivy, Michel; Dunand, Christophe; Albenne, Cécile; Jamet, Elisabeth
Abstract : Plant cell walls (CWs) contain a large proportion of polysaccharides (90–95% of CW mass) and proteins (5–10%) that play major roles in CW plasticity during development and in response to environmental cues. Here, we present CW proteomics data of Arabidopsis thaliana roots. Plants were cultivated in hydroponic conditions. CW protein (CWP) extracts were prepared and analyzed in two different ways in order to enlarge the coverage of the root CW proteome: proteins were analyzed either directly or following an affinity chromatography on a combinatorial peptide ligand library (CPLL) to reduce the concentration dynamic range. Proteins were identified by LC‐MS/MS and bioinformatics. Altogether, 424 proteins having predicted signal peptides have been identified (CWPs). CPLL permitted to identify low‐abundant CWPs never described before, thus enlarging the coverage of the root CW proteome. The number of oxidoreductases is particularly high and includes a large collection of class III peroxidases (CIII Prxs; 38 out of the 73 A. thaliana CIII Prxs). For the first time, hydroxyproline residues were localized at conserved positions in CIII Prx amino acid sequences.